Technical Reasoning on a Local Government Land Property as Heuristic Tool to Accommodate City Leaders Strategic Planning - Yasser Wahyuddin; Bambang Sudarsono (TEKNIK, 2021)
One of the Land Asset Management facets in Indonesia has been so far the possession of the land as an asset for local government. The regulation allows local government to organize local land assets to support land use planning in various patterns. While at the same time, Indonesia has a rigorous rule on land use planning with Euclidean Zoning System called RTRW Plan, which lasts for 20 years. Land use patterns could not be ruled by projecting a specific order, ideology, technical stances, etc. This article would like to contextualize a dynamic in which city leader infrastructure strategic planning was being technically anticipated by filtering out the feasibility of local land asset which meet the minimum requirement of the RTRW as the principal reference for spatial land use planning.  This article does not necessarily address its aim at problematizing RTRW; rather, in the first place, it discusses the vigorous of the local government technical department to bridge a so-called City Leader strategic planning with the current systems of the RTRW. Here, the article would argue that a tiny time frame of the City Leader's order leaves a narrow space for technical staff to map out a holistic technical plan. Instead, opting for a specific local land asset appeared to be the instant solution to such a plan. Furthermore, the second concern of this article specified its attention on providing the technical means so that the choice of the predetermined location was constructively and objectively justified beforehand.  A specific case study of Pekalongan Regency, Central Java Indonesia, allowed delving into the empirical case. The city leader was at the last year of his terms, and it was claimed, the choice to develop hospital infrastructure was part of a political maneuver. A qualitative approach in the form of in-depth interviews and compilation of secondary documents was employed. The city technical managers needed to operate rational technocratic mechanisms to the politico-technique juxtaposition to justify the planning problem's technical rationality and the other side to provide a technical solution, pointing out land assets under the framework of the RTRW. Thus, the arguments developed in this work contested the land choice technical assessments were not necessarily neutral rather a supporting element to adjust the overwhelming leader's strategic choice fully. Further discussion materials are proposed. In this case, the political strategy created a circumstance of instantaneity and a limited time frame that could lead to the enthusiasm of strategic thinking under the realm of the urban planning system.